Human Endometrial Extracellular Vesicles Functionally Prepare Human Trophectoderm Model for Implantation: Understanding Bidirectional Maternal‐Embryo Communication. Issue 23 (30th October 2019) - Evans, Jemma; Rai, Alin; Nguyen, Hong P. T.; Poh, Qi Hui; Elglass, Kirstin; Simpson, Richard J.; Salamonsen, Lois A.; Greening, David W.
Abstract: Embryo implantation into maternal endometrium is critical for initiation and establishment of pregnancy, requiring developmental synchrony between endometrium and blastocyst. However, factors regulating human endometrial–embryo cross talk and facilitate implantation remain largely unknown. Extracellular vesicles (EVs) are emerging as important mediators of this process. Here, a trophectoderm spheroid‐based in vitro model mimicking the pre‐implantation human embryo is used to recapitulate important functional aspects of blastocyst implantation. Functionally, human endometrial EVs, derived from hormonally treated cells synchronous with implantation, are readily internalized by trophectoderm cells, regulating adhesive and invasive capacity of human trophectoderm spheroids. To gain molecular insights into mechanisms underpinning endometrial EV‐mediated enhancement of implantation, quantitative proteomics reveal critical alterations in trophectoderm cellular adhesion networks (cell adhesion molecule binding, cell–cell adhesion mediator activity, and cell adherens junctions) and metabolic and gene expression networks, and the soluble secretome from human trophectodermal spheroids. Importantly, transfer of endometrial EV cargo proteins to trophectoderm to mediate changes in trophectoderm function is demonstrated. This is highlighted by correlation among endometrial EVs, the trophectodermal proteome following EV uptake, and EV‐mediated trophectodermal cellular proteome, important for implantation. This work provides an understanding into molecular mechanisms of endometrial EV‐mediated regulation of human trophectoderm functions—fundamental in understanding human endometrium–embryo signaling during implantation.